Futures, Visions, and Responsibility An Ethics of Innovation - Sand, Martin (Technikzukünfte, Wissenschaft und Gesellschaft / Futures of Technology, Science and Society, 2018)
Martin Sand explores the problems of responsibility at the early, visionary stages of technological development. He discusses the increasingly dominant concept of innovation and outlines how narratives about the future are currently used to facilitate technological change, to foster networks, and to raise public awareness for innovations. This set of activities is under increasing scrutiny as a form of "visioneering". The author discusses intentionality and freedom as important, albeit fuzzy, preconditions for being responsible. He distinguishes being from holding responsible and explores this distinction's effects on the problem of moral luck. Finally, he develops a virtue ethical framework to discuss visioneers' and innovators' responsibilities. Contents A Humanist Ethics of Innovation Responsibility and Visioneering Responsibility, Determinism, and Freedom Moral Luck and Intelligibility Collective and Corporate Responsibility The Virtues and Vices of Innovators Target Groups Researchers and students in the fields of technology assessment, ethics, philosophy Ethicists, policymakers, philosophers The Author Martin Sand completed his PhD at the Institute of Technology Assessment and Systems Analysis (ITAS) at the Karlsruhe Institute of Technology (KIT), Germany, under the supervision of Prof. Armin Grunwald and Prof. Ibo van de Poel (TU Delft).